Systematic Literature Review on The Role of Islamic Educational Values in Islamic Boarding Schools in Minimizing Negative Behavior Among Students - Lalu Pradipta Jaya Bahari (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2026)
This study is grounded in the growing concern over the rise of negative behaviors among students in the era of globalization and digital transformation, which increasingly challenge moral and ethical values within educational environments. Islamic boarding schools (pesantren), as traditional Islamic educational institutions, are considered to have a strategic role in addressing these challenges through the internalization of Islamic educational values. The urgency of this research lies in understanding how these values function not only as moral teachings but also as effective behavioral control systems in shaping students’ character. Therefore, this study aims to examine the role of Islamic educational values in minimizing negative behavior among students and to answer how these values are internalized and implemented within the pesantren context. This research employs a Systematic Literature Review (SLR) design by collecting and analyzing relevant scholarly articles from peer-reviewed journals. The data analysis involves identifying key themes, comparing findings across studies, and synthesizing a conceptual framework that explains the relationship between Islamic values and student behavior. The findings indicate that core Islamic educational values, such as honesty (ṣidq), responsibility (amānah), discipline (istiqāmah), and respect for teachers (ta‘dhīm al-ustādh) play a central role in reducing negative behaviors, including indiscipline, arrogance, and rule violations . These values are effectively internalized through three main mechanisms: the exemplary behavior of teachers (uswah hasanah), habituation through routine religious activities, and empathetic and participatory moral communication. The study demonstrates that Islamic education functions as a holistic moral control system that fosters self-regulation, moral awareness, and emotional balance among students. In conclusion, Islamic educational values significantly contribute to character formation and the prevention of negative behavior, reinforcing the role of pesantren as moral fortresses in the modern era. However, the study is limited by its reliance on secondary data and specific regional contexts; therefore, future research is recommended to conduct empirical field studies and comparative analyses to further validate and expand these findings.